Comparative analysis of polyester hydrolysis activity among three lipolytic enzymes. Issue 8 (7th June 2019) - Lin, Hong; Mu, Xiangduo; Huang, Jianzhong; Jiang, Hong; Niu, Jinghong; Shu, Zhengyu
Abstract: Background: Bacillus subtilis lipase (BSL), Burkholderia sp. lipase (BCL) and Ophiostoma piceae sterol esterase (OPE) represent three typical structural features of lipolytic enzyme active sites. In this research, enzymatic characterization, especially polyester degradation activity, of these lipolytic enzymes was conducted, which might give clues to enzymatic degradation of polyester plastics in the future. Results: The optimum temperatures of BSL, BCL and OPE were 40, 40 and 35 °C, respectively. The optimum pH of BSL, BCL and OPE were 8.0, 8.0 and 7.5, respectively. All three lipolytic enzymes displayed a preference for esters with medium acyl chain length (C8–C10). The initiation reaction rates towards poly( ϵ ‐caprolactone) hydrolysis catalyzed by BSL and BCL were 57 and 80 μg min −1  U −1, respectively. However, OPE showed very low activity towards poly( ϵ ‐caprolactone) degradation. In contrast, OPE displayed high activity towards poly(vinyl acetate) degradation. Conclusions: Poly( ϵ ‐caprolactone) could be enzymatically hydrolyzed using BSL and BCL, while poly(vinyl acetate) could only be enzymatically hydrolyzed using OPE. © 2019 Society of Chemical Industry